Penerapan Membaca Kreatif dalam Konversi Teks Berita Menjadi Cerpen pada Generasi Z - Nimas Ainaul Mardhiyah Hamir; Nisa Alliyah Rizqi Lutfiyah; Alvin Rahima Atha Widyatama; Farhan Razaqa Faubi; Muhammad Ibrasyam Al Auvar (Jurnal Pendidikan, Bahasa dan Budaya, 2026)
Language skills play a fundamental role in human communication and knowledge development. Among the four language skills, reading is a receptive skill that allows individuals to receive, comprehend, and interpret information through written texts. One approach that goes beyond mere comprehension is creative reading, which encourages readers to think critically, imagine, and generate new ideas based on texts they read. Generation Z, born between 1995 and 2010, is highly familiar with digital information, particularly news texts circulating through social media and online platforms. However, their reading activities have not been optimally utilized to produce creative literary works. This study aims to examine the application of creative reading in converting news texts into short stories among Generation Z. A descriptive quantitative method was employed involving 17 respondents selected through purposive sampling. Respondents were given digital news texts to convert into short stories, assessed using a rubric comprising five aspects: content relevance, creativity, intrinsic elements, language use, and coherence, with a maximum score of 25.